Different Wavelength Femtosecond Laser Pulses Generated by Diode Pumped Ti: Sapphire Crystal - Dhahir, Mohamed K. (Iraqi Journal of Laser, 2011)
The relation between the output power and wavelengths for a 532nm 3W frequency doubled diode pumped solid state laser pumped Ti:Sapphire crystal is investigated. A 20 femtosecond pulse at 800 nm is obtained. A 320 mW is found to be the highest power at 800nm. Below this wavelength value and above the power was found to deviate from highest output value.